2005
DOI: 10.1542/peds.2004-1064
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Femur Fractures, Associated Injuries, and Sociodemographic Risk Factors: A Population-Based Study

Abstract: ABSTRACT. Objective. The objectives of this study were to determine the incidence of femur fractures in Colorado children, to assess underlying causes, to determine the prevalence and predictors of associated injuries, and to identify potentially modifiable risk factors.Methods. The study population included all Colorado residents who were aged 0 to 17 years at the time of injury between January 1, 1998, and December 31, 2001. Cases of femur fracture were ascertained using the population-based Colorado Trauma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
57
0
8

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(71 citation statements)
references
References 54 publications
(61 reference statements)
6
57
0
8
Order By: Relevance
“…Few previous studies report fracture as an injury outcome but our findings with respect to child age are consistent with those that do, such as Flavin et al [38]. Our findings with respect to child sex are consistent with studies of thermal injuries and fractures [19,32,[47][48][49]. We did not find an association between sex and poisoning, which is consistent with data reported by Beautrais et al [20] and with the poisoning incidence statistics reported by the World Health Organisation, which showed only a small (0.1/100,000) difference in poisoning rates in Europe between boys and girls [2].…”
Section: Comparisons With Other Studiessupporting
confidence: 92%
“…Few previous studies report fracture as an injury outcome but our findings with respect to child age are consistent with those that do, such as Flavin et al [38]. Our findings with respect to child sex are consistent with studies of thermal injuries and fractures [19,32,[47][48][49]. We did not find an association between sex and poisoning, which is consistent with data reported by Beautrais et al [20] and with the poisoning incidence statistics reported by the World Health Organisation, which showed only a small (0.1/100,000) difference in poisoning rates in Europe between boys and girls [2].…”
Section: Comparisons With Other Studiessupporting
confidence: 92%
“…All fracture patterns (transverse, spiral, and comminuted) can occur in abuse. Only 12% to 13% of femur shaft fractures are due to abuse in children younger than 3 years [4,19]. In children younger than 1 year, up to 30% of femur fractures are reportedly from abuse [12].…”
Section: Orthopaedic Manifestations Of Abusementioning
confidence: 99%
“…As mentioned earlier, Loder and Bookout [21] reviewed 75 cases of battered children with a total of 154 fractures and found the most common long bone fracture was transverse shaft fractures, followed by CMLs. Rewers et al [31] conducted a review of the cases with documented femoral fractures entered into the Colorado Trauma Register over a 4-year period. They found that among children younger than 3 years, falls were the most common cause of femoral fractures, followed by nonaccidental injury.…”
Section: Accidental Versus Nonaccidental Injurymentioning
confidence: 99%